Effects of Trachyspermum copticum L. on Morphine\'sWithdrawal Syndrome Signs in rats - H Jaffari; M Shahidi; S.R Miri; R Gharebaghi; S Yadegari (Institue of Medicinal Plants, ACECR, 2004)
Drug addiction is destructive misfortune. At the present time we have over 1.2 million addicted people in Iran. So, proper and definite treatment must be noticed. Using the medical plants in ancientness like human life and thousand documents in medicinal history have valuable informations and expriments in this field. According to extant investigations, Trachyspermum copticum has numerous effects, such as antiseptic, expectorant, Spasm relaxation and useful in cholesteralemia. But in the belief of Iranian people, this plant is used for treatment of addiction. This project is the first investigation in the world that Iranian researchers evaluated the effect of trachyspermum copticum extract in treatment of morphine dependency. After preparing the trachyspermum copticum fruit from height of the mountain in KHozestan (between izeah and dehdaz), aqueous extract at different concentration (10%, 20%, 30%) was prepared by suckcele display. After the pilot study, 5 groups (50 rats) were dependent by subcotaneus injection with morphine. After insuring the animal dependency. First group has set as a testifire. Second group was affected with methadon treatment and other groups were treated by trachyspermum copticum at different concentration (10%, 20%, 30%). In all groups after naloxane injection by intraperitoneum injection, we studies morphine dependency that manifestated like diarrhea, weight loss and jumping. At 30% concentration, seven animals were deaed for the reason high concentration of extract. Data evaluation with ANOVA and LSD test showed that trachyspermum copticum is effective like methadone therapy to decrease withdrawal syndrome signs (p<0.05).